DARURAT KORUPSI (KEPALA) DAERAH PASCA PEMILUKADA - Hadinata, Khrisna (JURNAL KONSTITUSI, 2011)
General election of regional leader in the reality does not at moments notice bear regional leader, which is have integrity to and blessing to aspiration and importance of people. All enforcer punish even also looked to be at the end of ones rope finish case badness of corruption entangling all authoritarians of this state and his partner. Equally law, enforcer punishes and our culture still not yet can give to have cold feet people who conduct badness of corruption.Â